Functional and Structural Network Disorganizations in Typical Epilepsy With Centro-Temporal Spikes and Impact on Cognitive Neurodevelopment - Bourel-Ponchel, Emilie; Mahmoudzadeh, Mahdi; Adebimpe, Azeez; Wallois, Fabrice (Frontiers in Neurology, 2019)
Epilepsy with Centrotemporal Spikes (ECTS) is the most common form of self-limited focal epilepsy. The pathophysiological mechanisms by which ECTS induces neuropsychological impairment in 15–30% of affected children remain unclear. The objective of this study is to review the current state of knowledge concerning the brain structural and functional changes that may be involved in cognitive dysfunctions in ECTS. Structural brain imaging suggests the presence of subtle neurodevelopmental changes over the epileptogenic zone and over distant regions in ECTS. This structural remodelling likely occurs prior to the diagnosis and evolves over time, especially in patients with cognitive impairment, suggesting that the epileptogenic processes might interfere with the dynamics of the brain development and/or the normal maturation processes. Functional brain imaging demonstrates profound disorganization accentuated by IES in the epileptogenic zone and in remote networks in ECTS. Over the epileptogenic zone, the literature demonstrates the existence of local synchronization/desynchronization and higher levels of neuronal activity which are effective several hundred milliseconds before the IES. In the same time window, desynchronization and changes in neuronal activity are also observed in bilateral distant networks, notably in the frontal and temporal lobes. This is associated with alteration of global small-world properties towards a more random network. The direction of information flow between the various brain regions demonstrates that, in ECTS, the epileptogenic zone constitutes the key area at the origin of IES propagation towards distant cortical regions, including frontal areas. Altogether, structural and functional network disorganizations, in terms of: (i) power spectral values, (ii) functional and effective connectivity, are likely to participate in the cognitive impairment commonly reported in children with ECTS. These results suggest a central and causal role of network disorganizations related to IES in the neuropsychological impairment described in ECTS children.